KLASSP: Entering Passwords on a Spyware Infected Machine Using a Shared-Secret Proxy - Florencio, Dinei; Herley, Cormac (Association for Computing Machinery, Inc., 2006)
In this paper we examine the problem of entering sensitive data, such as passwords, from an untrusted machine. By untrusted we mean that it is suspected to be infected with spyware which snoops on the user’s activity. Using such a machine is obviously undesirable, and yet roaming users often have no choice. They are in no position to judge the security status of internet cafe, airport lounge or business center machines. Either malice or negligence on the part of an administrator means that any such machine can easily be running a keylogger. The roaming user has no reliable way of determining whether it is safe, and has no alternative to typing the password. We consider whether it is possible to enter data to confound spyware assumed to be running on the machine in question. The diﬃculty of mounting a collusion attack on a single user’s password makes the problem more tractable than it might appear. We explore several approaches. In the ﬁrst, we show how the user can embed a password in random keystrokes to confuse spyware, while leaving the actual login unaﬀected. In the second we employ a proxy server to strip random keys. In the third we again employ a proxy that inverts a key mapping performed by the user. We examine also several potential attacks.